Tantangan Pendidikan Agama Islam Dalam Era Global - Nurhilaliyah (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
In this era of globalization, Islamic Education poses new challenges coupled with modern day technological advancements, cultural shifts and the rapid flow of information. Globalization on the one hand, has positive consequences such as wider perspectives, ease of information and easier access to knowledge. At the same time, it has dire consequences such as the moral crisis of secularization coupled with ideologies, emerging of new ideologies working against the Islamic sentiment. The fundamental challenges of PAI as poorly integrated curriculum to contemporary needs, character related to the positive information deluge, and the fast growing teacher, discretely and profoundly integrating spirituality with the 21st century skill. Hence, it has become paramount to explore PAI curricula that go beyond the fundamental Islamic knowledge as to sustain positive Islamic as well as moral values and character, foster critical citizenship, and prepare students to partake on the Islamic world stage as a competing premier nation.